2011
DOI: 10.1016/j.amc.2011.04.075
|View full text |Cite
|
Sign up to set email alerts
|

Optimal inspection policy for three-state systems monitored by control charts

Abstract: This paper presents the formulations of the expected long-run cost per time unit for a system monitored by a static control chart and by an adaptive control chart respectively. The static chart has a fixed sampling interval and a fixed sample size. The adaptive chart has a fixed sample size but variable sampling intervals. The system is supposed to have three states, normal working state, failure delay time state, and failed state. Two levels of repair are used to maintain the system. A minor repair is used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…However, in practice we have observed that there are mostly just one or two thresholds. A two-threshold policy defines a three-state process that was popularly accepted and used in CM practice and in most CM related literature (Christer & Wang 1995;Wu & Wang, 2011). This problem can be observed in reality, e.g., in induction furnaces, battery systems, motors, industrial pumps and bearings.…”
Section: Problem Descriptionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, in practice we have observed that there are mostly just one or two thresholds. A two-threshold policy defines a three-state process that was popularly accepted and used in CM practice and in most CM related literature (Christer & Wang 1995;Wu & Wang, 2011). This problem can be observed in reality, e.g., in induction furnaces, battery systems, motors, industrial pumps and bearings.…”
Section: Problem Descriptionmentioning
confidence: 98%
“…However, the inspection defined in Jiang's paper is the action used to obtain the accurate CM measurement rather than the manual inspection defined in our paper. Moreover, Wang (2011b) and Wu and Wang (2011) used a similar idea to ours when modeling two types of errors in statistical quality control.…”
Section: Introductionmentioning
confidence: 95%
“…In their model, the time of shift to an out-of-control condition and the time of equipment failure are assumed to be two different random variables. Panagiotidou and Nenes [20] and Wu and Wang [21] improved the integrated model in terms of the monitoring method and they replaced the traditional static fixedparameter (Fp) Shewhart control chart by employing an adaptive variable-parameter (Vp) Shewhart control chart with PM to monitor process mean. Kuo [22] and Xiang [23] formulated the deterioration process as a discrete-time Markov chain and jointly optimized the integrated model of SPC and maintenance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Delay‐time–based PM models differ from other PM models in that they directly model the relationship between PM and the number of system failures. Many case studies have shown the validity of such models …”
Section: Introductionmentioning
confidence: 99%